Calculation of parameters of vegetable raw materials subdrying - A. N. Dadyko (Сельскохозяйственные машины и технологии)
The authors described properties of the vegetable waste (VW) as object of burning in fire chambers of grain dryers. Though VW are often characterized by low combustion heat (10-12 MJ per kg), they could be considered as the valuable low-ash biological fuel which almost not contain ssulphur compounds and not pollute environment at the correct organization of burning process. Burning in a low-temperature circulating and vortex layer allows to keep small particles (0.5-3.0 mm) in a reaction zone before full burning out. Low-temperature condition of burning (600-700 degrees Celsius) excludes slagging of surfaces of a fire chamber, including heatexchange ones, and also reduces poison emission in the atmosphere. Precede subdrying of the VW particles and burning period have often the same duration. Duration of subdrying is calculated on the basis of the heatmass transfer equations. Transfer of heat when subdrying of small particles (less than 0.5-1.0 mm) is carried out by heat conductivity, when large particles (more than 1.0 mm) subdrying this process is convective. Adequacy of calculation formulas was estimated by the available experimental results of VW particles burning. Satisfactory coincidence (12 percent measure of inaccuracy) is received. The same coincidence is characteristic for calculated dependence at the equivalent coefficient of heat conductivity which value exceeds a table one by 25 percent. If a fuel is low-reactionary and solid, with a caloric content of 15 MJ per kg so burning of it in the furnace block aggregated with a grain drayer will be better at addition of high-reactionary liquid or gaseous fuel.